2020
DOI: 10.1108/scm-09-2019-0327
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation, knowledge acquisition and collaborative performance in agri-food value-chains in emerging markets

Abstract: Purpose This study aims to take a whole-of-chain perspective to explore how entrepreneurial orientation (EO) influences collaborative performance in agri-food value-chains through enhancing the acquisition of knowledge. Design/methodology/approach Data were collected through a survey of 233 actors, including farmers, intermediaries and retailers in one beef cattle value-chain in the Central Highlands, Vietnam. Structural equation modeling was used to test hypotheses. Findings The actors’ level of EO within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 99 publications
(146 reference statements)
1
26
0
Order By: Relevance
“…However, for acquiring satisfactory resources, they must have abilities like innovativeness, risk‐taking, and proactiveness (Teng, 2007; Wilson & Appiah‐Kubi, 2002). EO assists ventures in acquiring external and useful information that is used for high‐performance activities (Dung, Bonney, Adhikari, & Miles, 2020). Factors such as discovering opportunities mediate the relationship between newly‐established firms and new venture performance (Donbesuur, Boso, & Hultman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for acquiring satisfactory resources, they must have abilities like innovativeness, risk‐taking, and proactiveness (Teng, 2007; Wilson & Appiah‐Kubi, 2002). EO assists ventures in acquiring external and useful information that is used for high‐performance activities (Dung, Bonney, Adhikari, & Miles, 2020). Factors such as discovering opportunities mediate the relationship between newly‐established firms and new venture performance (Donbesuur, Boso, & Hultman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of emerging economies, researchers believe that perhaps the most potent cause of early failure of new ventures is a lack of entrepreneurial skills (Adomako, Danso, Boso, & Narteh, 2018). Several studies conducted in developing countries have confirmed that entrepreneurial orientation (EO) is a significant predictor of venture performance (Anwar, Khan, & Khan, 2018; Cassia & Minola, 2012; Dung, Bonney, Adhikari, & Miles, 2020; Kohtamäki, Heimonen, & Parida, 2019; Raisal, Tarofder, & Ilmudeen, 2021). Some studies have found a direct relationship between EO and performance (Alarape, 2013; Kraus, Rigtering, Hughes, & Hosman, 2012; Lomberg, Urbig, Stöckmann, Marino, & Dickson, 2017) while others have claimed an indirect relationship (Jiang, Liu, Fey, & Jiang, 2018; Karami & Tang, 2019; Kohtamäki, Heimonen, & Parida, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers believe that motivation is more significant than entrepreneurial behavior because EO is not only a key influencing factor on the entrepreneurial process but also determines whether a new project will be successful [27]. Specifically, empirical evidence exists of a positive relationship between EO and farmers' performance [28]. Therefore, EO is a crucial factor that is not only affected by rapidly changing external factors but also affects entrepreneurship and plays a vital role in the prosperity of farmers [29].…”
Section: B Mediating Role Of Farmers' Eomentioning
confidence: 99%
“…The challenge is no longer within the value chains, but also, within the supply chains and value chains connections. New entrepreneurial behaviours are approached where knowledge acquisition and collaborative performance are brought together (Dung, 2020). Moreover, there are opinions that put into discussions the green value chain innovation (Huiling, 2020), so that modern business models to be energy efficient and less polluting.…”
Section: Problem Statementmentioning
confidence: 99%